Evaluation of the prevalence of sagittal plane changes in the spine of elementary students in the city of Ceres, Brazil (Research, Society and Development, 2021)
Background: Adolescence is the period when postural changes occur, as it is a phase when the body develops and grows. It is also the most appropriate time to evaluate and detect postural problems, and preventive measures may help to avoid these possible changes. However, studies evaluating the postural changes in this age group are lacking. Objective: The objective of this study was to evaluate thoracic kyphosis and lumbar lordosis changes in the spine of 9th grade students at a state military school in Goiás, Brazil. Methods: A total of 113 students (54 boys and 59 girls) participated in the study. A radiation-free three-dimensional scanning system was used to evaluate the students’ spine. The equipment emits a light on the participants’ back and uses its topography to automatically calculate asymmetries. Results: The prevalence of increased thoracic kyphosis was 14%, increased lumbar lordosis 2% and 72% straightening of the curvature of the lumbar lordosis. Thoracic kyphosis was reported by 9% of male students and 19% of female students. Students of both sexes had increased lumbar lordosis (2%). Females had a higher prevalence of rectified lumbar lordosis (59%) than males (11%). Conclusion: The prevalence of postural changes, especially lumbar lordosis, was very high in the elementary students.